PENGARUH LIKUIDITAS, LEVERAGE DAN PROFITABILITAS TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Purba, Rolita Christina (JURNAL NERACA AGUNG, 2020)
Financial distress is a condition where the company's finances are not in a bad condition, but have not gone bankrupt. Therefore, companies need to identify the condition of financial distress as an evaluation. This study aims at examining the effect of liquidity proxied by current ratio (CR), leverage proxied by debt to equity ratio (DER) and profitability proxied by return on assets (ROA) on financial distress in mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2019 period. The population in this study are all companies in the mining sub sector listed on the Stock Exchange as many as 22 companies. The sampling technique in this study is purposive sampling, so that the sample of this study were 15 companies. This analysis method uses linear regression.